(untitled) (Research, Society and Development, 2024)
Objective: To correlate spirituality/religiosity and quality of life within the university atmosphere of a Brazilian medical school. Methodology: Cross-sectional and observational study with 176 medical students from the Faculdade de Medicina do Mucuri at the Universidade Federal dos Vales do Jequitinhonha e Mucuri in 2020. The data collection instruments were: a sociodemographic questionnaire; the Spiritual Well-Being Scale (SWBS) to assess spiritual, religious and existential well-being; and the World Health Organization Quality of Life bref (WHOQOL-bref) to assess students’ quality of life. Data were analyzed according to descriptive statistics, Cronbach’s Alpha, Mann-Whitney test, Kruskal-Wallis test, and Spearman’s correlation. Results: The students had moderate spiritual and existential well-being and high religious well-being. The quality of life assessment showed satisfaction in the psychological and environmental domains and high satisfaction in the physical, social and general domains. Conclusion: In the medical course, students encounter challenging situations that shape them for the future, but everyone carries their own set of beliefs, meanings of life and certainties and this affects their quality of life and spiritual well-being. The pandemic period is an important interfering factor in the data in this study.